All Days 2013
DOI: 10.2118/168084-ms
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Integration of Streamline Information in Finite Difference Simulation during Optimization to Enhance History Matching

Abstract: Matching water cuts of production wells is one of the most challenging tasks in the history matching process. When conducting history matching with a finite difference simulator, one of the challenges is how to define a suitable region for the permeability modifier to obtain a good match, and yet, retain major geological description. In the case of large models, the presence of several wells in a region where permability is adjusted makes simultaneous matching for these wells almost impossible. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 11 publications
2
79
0
Order By: Relevance
“…The ADA and USPSTF recommend that diabetes screening occur in a health care setting where testing is "opportunistic," or obtained when patients present to the health care system for reasons unrelated to diabetes screening (1,2,6). Estimates of opportunistic screening rates in clinical practice vary from 6 to 24% and identify significant missed screening opportunities (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The ADA and USPSTF recommend that diabetes screening occur in a health care setting where testing is "opportunistic," or obtained when patients present to the health care system for reasons unrelated to diabetes screening (1,2,6). Estimates of opportunistic screening rates in clinical practice vary from 6 to 24% and identify significant missed screening opportunities (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The rapid growth in EC use is linked to advertising and promotion marketing campaigns (51,52) which have likely contributed to increasing favorable perceptions, even among pregnant women. Indeed, EC are thought to be a safer alternative to conventional cigarettes and to help women quit smoking in pregnancy (53), although it has not been demonstrated that using them is effective with regard to the latter (54). Women may be attracted to the flavorings due to alterations in taste that they generally experience during pregnancy (55).…”
Section: Parental Attitudes Toward Ec Use and Perception Of Children's Health Risks Connected To Ec Exposurementioning
confidence: 99%
“…Breast cancer is the most common-invasive cancer in women worldwide, affecting 1 in 7 women (7,8). For women of average risk, the U.S. Preventive Services Task Force (USPSTF) and American College of Physicians (ACP) recommends mammography every two years in women between the ages of 50 and 74 (9). When diagnosed early, breast cancer is curable with a multimodal approach to therapy, even for cancers that have high risk molecular profiles.…”
Section: Breast Cancermentioning
confidence: 99%
“…Currently, the USPSTF recommends mammography every two years in women between the ages of 50 and 74 (9). Unfortunately, disparities are evident in completion of screening mammography due to lower SES (including income, race, and ethnicity).…”
Section: Screening and Stage Of Presentationmentioning
confidence: 99%